Terminal glycosylation of bovine uroplakin III, one of the major integral-membrane glycoproteins of mammalian bladder - Malagolini, Nadia; Cavallone, Daniela; Wu, Xue-Ru; Serafini-Cessi, Franca (Biochimica et biophysica acta, 2000)
Uroplakin III (UPIII) is one of the major transmembrane glycoproteins exposed at the luminal face of mammalian bladder. We investigated the terminal glycosylation of bovine UPIII in order to ascertain whether it contains the α2,3-sialylated sequence thus potentially serving as a receptor for uropathogenic Escherichia coli expressing type S adhesins. We report the occurrence of sialic acid in α2,3- and α2,6-linkage to galactose in bovine UPIII glycans as evidenced by the sensitivity of UPIII to both Vibrio cholera and Newcastle disease virus neuraminidase and by the colocalization of UPIII antigen and material detected by lectins of Sambucus nigra and Maackia amurensis on the luminal face of the bladder. We also present evidence that UPIII glycans are capped by Gal-α1,3-Gal epitope. Consistently, α2,3- and α2,6-sialyltransferase, as well as α1,3-galactosyltransferase were found to be present in the cells detached from the luminal side of bovine bladder, which are responsible for the UPIII biosynthesis. The putative role of UPIII sialylated glycans in enhancing the uropathogenicity of E. coli expressing type S adhesins is discussed.